EVALUASI KEGIATAN SIMPAN PINJAM PEREMPUAN PADA PNPM MANDIRI PERKOTAAN DI KAMPONG KAMPUNG BARU KOTA SUBULUSSALAM PROVINSI ACEH - Muhamad Nur Afandi (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2013)
eople empowerment is closely related to handling matters of development, the problem of unemployment, poverty and inequalities. Poverty eradication policy cannot be separated from context of the society. The development so far is toachieve better conditions. Urban community empowerment (PNPM MP) is one of the Government programs to accelerate poverty eradication through among others provision of credits for women (SPP). The activities credits for women (SPP) have also been implemented in Subulussalam City. The study is done inKampong Kampung Baru Kecamatan Penanggalan that is one the area of Subulussalam. The respondents of this research are members of SPP in urban community empowerment (PNPM MP) program. The research aims at evaluating the implementation of SPP activities starting in 2009 to 2012. The variables of this research are out-put evaluation, benefit evaluation, and impact/outcome evaluation. This research uses descriptive methods with a qualitative approach, while the technique of the data collection uses interview, observation, and documentation. The results of research studies have been carried out on the implementation of SPP as follows: (1) Implementation of SPP activity has not been optimal, this happens because of economic trouble experienced by members of the SPP. Loans for working capital used to help meet the basic needs of the family. (2) There are several obstacles encountered in the implementation of SPP, ie: the credit crunch, the selection of the type of business that is not appropriate, the level of participation of members of the SPP are still low in following socialization and training. (3) The government has made efforts to overcome the obstacles in the implementation of SPP, ie: the dissemination of the essence of the SPP activities, motivating, training continuously.